Badminton Sports Techniques and Learning Methods - Yerixonovich, Tashmuratov Farrux (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article, modern badminton also has a lot of action skills. Participants are required to develop specialized strength, agility, endurance, agility, flexibility, willpower, tenacity, sharp wit, intelligence, "cunning" (in the sense of good sports) and other similar qualities.